Focal Geometry and Characteristics of Erosion-Prone Coronary Plaques in vivo Angiography and Optical Coherence Tomography Study - Cao, Muhua; Wu, Tianyu; Zhao, Jiawei; Du, Zhuo; Wang, Zhuozhong; Li, Lulu; Wei, Guo; Tian, Jinwei; Jia, Haibo; Mintz, Gary S.; Yu, Bo (Frontiers in Cardiovascular Medicine, 2021)
Objective: This study compared focal geometry and characteristics of culprit plaque erosion (PE) vs. non-culprit plaques in ST-segment elevated myocardial infarction (STEMI) patients in whom optical coherence tomography (OCT) identified PE as the cause of the acute event. Background: Culprit PE is a distinct clinical entity with specific coronary risk factors and its own tailored management strategy. However, not all plaques develop erosion resulting in occlusive thrombus formation. Methods: Between January 2017 and July 2019, there were 484 STEMI patients in whom OCT at the time of primary percutaneous intervention identified culprit lesion PE to be the cause of the event; 484 culprit PE were compared to 1,132 non-culprit plaques within 1,196 imaged vessels. Results: Culprit PE were highly populated at “hot spots” within the proximal 40 mm in the left anterior descending artery (LAD) and tended to cluster proximal to a nearby bifurcation mainly in the LAD. Minimal lumen area (MLA) <2.51 mm2 and AS (area stenosis) >64.02% discriminated culprit PE from non-culprit plaques. In the multivariable analysis, focal geometry (LAD location, distance from coronary ostium <40 mm, and location proximal to a nearby bifurcation), luminal narrowing (MLA <2.51 mm2, AS > 64.02%), and TCFA phenotype were independent predictors of culprit PE overall. Cholesterol crystals were predictive of culprit PE with underlying LRP morphology while the absence of calcification and microchannels were risk factors for culprit PE with an underlying non-LRP. Similarities and differences in predictors of culprit PE were found between males and females; distance from coronary ostium <40 mm, MLA <2.51 mm2, TCFA, and less spotty calcium were risk factors of culprit PE in males, but not in females while smaller RVD was associated with culprit PE only in females. Conclusions: Irrespective of underlying lesion substrates and patient risk factors, there are lesion-specific and OCT-identifiable predictors of developing culprit PE in erosion-prone vulnerable patients.